Analisis Antisipasi Puskesmas Akan Tanggap Darurat Bencana Kebakaran - Mutiara Ashifa; Fatma Salsabila; Nurly Fadila; Susilawati; Abdurrozzaq Hasibuan (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Puskesmas is a formal sector that is very likely to occur in the event of a fire disaster.  Workers who work in the formal sector such as puskesmas have a lurking threat that can pose a risk to their work environment. Anticipation of K3 Emergency Response (Occupational Safety and Health) is mandatory. So, it is important for puskesmas to implement K3 and prepare emergency response that can prevent disasters such as fire. The purpose of this article is to find out the analysis of the anticipation of puskesmas on fire disaster emergency response.  The method used to collect information is the literature view methodology through sources from online media such as Mendeley, Google Schoolar, Publish or Perish, and other online media. Based on articles that have been collected from 14 analyzed articles. The results of the literature study analysis were obtained that the human resources of most puskesmas already have a special disaster emergency response team, for the budget using funds from the puskesmas, then in facilities and infrastructure some are sufficient such as alarms, fire detectors, and evacuation support. Anticipation of fires in each puskesmas has carried out the standards of the Ministry of Health.